2018
DOI: 10.1194/jlr.m087387
|View full text |Cite
|
Sign up to set email alerts
|

Intervention with citrus flavonoids reverses obesity and improves metabolic syndrome and atherosclerosis in obese Ldlr−/− mice

Abstract: Obesity and its associated metabolic dysfunction and cardiovascular disease risk represent a leading cause of adult morbidity worldwide. Currently available pharmacological therapies for obesity have had limited success in reversing existing obesity and metabolic dysregulation. Previous prevention studies demonstrated that the citrus flavonoids, naringenin and nobiletin, protect against obesity and metabolic dysfunction in mice fed a high-fat cholesterol-containing (HFHC) diet. However, their effects in an int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
73
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 96 publications
(74 citation statements)
references
References 47 publications
1
73
0
Order By: Relevance
“…Furthermore, other therapeutics that work by promoting increased energy expenditure do so by enhancing the thermogenic capacity of brown or beige adipose tissue without effect on food intake. The results of the present studies and our previous studies suggest that it is unlikely that naringenin works through either of these mechanisms . In lean chow‐fed mice, naringenin stimulated a small increase in food intake, rather than appetite suppression and no evidence of adipose tissue browning has been consistently detected.…”
Section: Discussionsupporting
confidence: 53%
See 3 more Smart Citations
“…Furthermore, other therapeutics that work by promoting increased energy expenditure do so by enhancing the thermogenic capacity of brown or beige adipose tissue without effect on food intake. The results of the present studies and our previous studies suggest that it is unlikely that naringenin works through either of these mechanisms . In lean chow‐fed mice, naringenin stimulated a small increase in food intake, rather than appetite suppression and no evidence of adipose tissue browning has been consistently detected.…”
Section: Discussionsupporting
confidence: 53%
“…Reduced food consumption persisted for four weeks before becoming isocaloric thereafter, resulting in non‐different overall food consumption between the two groups over 8 weeks (Figure G). In previous mouse regression studies, we observed a taste aversion during the transfer of mice from a high‐fat diet to a naringenin supplemented chow diet (data not shown), but not with a naringenin supplemented high‐fat diet, providing a likely explanation for the initial 4‐week decrease in caloric intake (Figure G).…”
Section: Resultsmentioning
confidence: 57%
See 2 more Smart Citations
“…In recent years, naringenin has been shown to exert a range of biological effects, including anti‐inflammation (Jin, Zeng, Zhang, Zhang, & Liang, ), anti‐oxidation (Zhao et al, ), hypolipidaemic effects (Mulvihill et al, ), immunoregulation (Zeng et al, ), and antineoplastic activity (Ke et al, ). Moreover, naringenin ameliorated obesity (Burke et al, ), metabolic syndrome (Alam et al, ), diabetes (Al‐Dosari, Ahmed, Al‐Rejaie, Alhomida, & Ola, ), and atherosclerosis (Mulvihill et al, , a). We have found that naringenin attenuated the hepatic lipid accumulation induced by a methionine‐choline deficient (MCD) diet in mice (Chen et al, ).…”
Section: Introductionmentioning
confidence: 99%